Stalno izobraževanje učiteljev in učiteljic nemščine kot del vseživljenjskega učenja - Kosevski Puljić, Brigita (Vestnik za tuje jezike, 2010)
Permanent teacher training means life-long learning for professional development based on new recognitions regarding the autonomy of open professionalism. The purpose of permanent training is mainly following the objectives of the subject matter of the profession, students' needs, and new approaches to teaching and learning. The centre of the teaching profession should be the processes of teaching and learning where teachers appear as professionals for classroom teaching and are capable of using critical thinking as part of the learning process. A wish for professional training in the form of institutional permanent training is present among the majority of teachers; however, it is limited by finances and time. This paper presents some opinions of teachers of German language from an evaluation regarding their permanent professional training. It can be concluded that permanent professional training needs a renovation in its structure and implementation to incorporate the new recognitions of the needs of the professional teacher.
Keywords: izobraževanje učiteljev; stalno strokovno izpopolnjevanje; učitelji nemščine; pouk; evalvacija